2015
DOI: 10.3310/hsdr03170
|View full text |Cite
|
Sign up to set email alerts
|

Service user engagement and health service reconfiguration: a rapid evidence synthesis

Abstract: BackgroundUK NHS organisations are required to consult patients and the public about proposals for major changes to services. The evidence base for current UK guidance is unclear.ObjectivesTo assess what is known about effective patient and public engagement in reconfiguration processes and to identify implications for further research.DesignRapid evidence synthesis.SettingHealth services affected by reconfiguration proposals in the UK (particularly the English) NHS and similar health systems.ParticipantsMembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 19 publications
0
24
0
2
Order By: Relevance
“…As it has been widely claimed, it is vital that mental health services are planned and offered taking into account service users' views and recommendations, as their engagement is crucial for their successful delivery (Dalton, Chambers, Harden et al, 2016). This is especially the case with young people in the care system, who might often feel disempowered and have little control of their lives, and whose emotional wellbeing should not be overlooked.…”
Section: Resultsmentioning
confidence: 99%
“…As it has been widely claimed, it is vital that mental health services are planned and offered taking into account service users' views and recommendations, as their engagement is crucial for their successful delivery (Dalton, Chambers, Harden et al, 2016). This is especially the case with young people in the care system, who might often feel disempowered and have little control of their lives, and whose emotional wellbeing should not be overlooked.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have evaluated different types of CE interventions that have been implemented with the aim of improving local health and care services or neighbourhoods’ healthy living infrastructure [ 9 – 12 ]. Earlier literature reviews have focused on how CE interventions affect populations’ health and social outcomes [ 8 , 13 ] or organisational structures and processes [ 14 , 15 ]. Each of these studies has shed some light on the problems that prevent CE interventions from reaching ‘meaningful’ citizen participation.…”
Section: Introductionmentioning
confidence: 99%
“…4 In response, studies have suggested involvement practices which might allow change to proceed, including: involving a wide range of stakeholders, early and prolonged engagement, and emphasizing clinical rationales for change processes. 5,6 These recommendations are in line with a wider view of public involvement as a coherent intervention with shared meaning which can bridge the troubled waters of service reconfiguration. The terminology of 'involvement' nevertheless masks a wide and even conflicting range of practices and purposes.…”
Section: Introductionmentioning
confidence: 67%